Methods for assessing business reputation company (Journal of Economic Research & Business Administration, 2015)
In the state considered a set of methods for evaluation value of goodwill. Advantages and disadvantages of the methods, ways to increase the value of goodwill for the company. Management decisions need to know as goodwill affect the value of the company in the future. Companies need a management system that addresses the role of intangible assets, including goodwill in the formation of their value. Currently, additional profi t companies brings the effective use of intangible assets.
Keywords: business reputation; risk of business reputation loss; goodwill; brand